Protein and peptide delivery to lungs by using advanced targeted drug delivery. (5th January 2022) - Chellappan, Dinesh Kumar; Prasher, Parteek; Saravanan, Vilashini; Vern Yee, Vanessa See; Wen Chi, Wendy Chai; Wong, Jia Wei; Wong, Joon Kang; Wong, Jing Tong; Wan, Wai; Chellian, Jestin; Molugulu, Nagashekhara; Prabu, Sakthivel Lakshmana; et al.
Abstract: The challenges and difficulties associated with conventional drug delivery systems have led to the emergence of novel, advanced targeted drug delivery systems. Therapeutic drug delivery of proteins and peptides to the lungs is complicated owing to the large size and polar characteristics of the latter. Nevertheless, the pulmonary route has attracted great interest today among formulation scientists, as it has evolved into one of the important targeted drug delivery platforms for the delivery of peptides, and related compounds effectively to the lungs, primarily for the management and treatment of chronic lung diseases. In this review, we have discussed and summarized the current scenario and recent developments in targeted delivery of proteins and peptide-based drugs to the lungs. Moreover, we have also highlighted the advantages of pulmonary drug delivery over conventional drug delivery approaches for peptide-based drugs, in terms of efficacy, retention time and other important pharmacokinetic parameters. The review also highlights the future perspectives and the impact of targeted drug delivery on peptide-based drugs in the coming decade. Highlights: Prominence of pulmonary drug delivery over the other modes of administration. Pulmonary delivery of Protein/peptide-based biologics for optimal pharmacokinetics. Translational efficacy of protein/peptide-based therapeutics for clinical advancement. Drug conjugated protein/peptide biologics to restore an optimal respiratory health.